A new species of Apecholinus Bernhauer, 1933 (Coleoptera: Staphylinidae: Staphylininae) from Mangshan, China - Sun, Wan-Wan; Jiang, Fei-Yan; Chen, Gang; He, Lin; Liu, Zhi-Ping (Zootaxa, 2024)
A new species, Apecholinus speciosus Sun & Liu, sp. nov. collected from Mangshan, Hunan Province, China, is described. Illustrations of taxonomically important characters and photographs of the habitus are provided. The new species is compared to Apecholinus imitator Smetana & Hu, 2019. The complete mitochondrial genome of A. speciosus was sequenced, assembled, and annotated. Phylogenetic analysis based on mitochondrial genomes showed that two Apecholinus species form a clade sister to Ocypus and Dinothenarus, and they all belong to the Ocypus lineage.